The Study of Factors That Effectively Reduce the Risk and Accident in Construction Project - Dzul Ghaffar, Muhammad Syamir (Universiti Teknologi PETRONAS, 2019)
The construction sector is a major job sector in Malaysia. It aims to provide the infrastructure needed by the people while at the same time contributing to the country's economic growth rate. However, this sector is always exposed to hazards and frequent accidents. The risk and accidents in construction projects are a serious problem that often occurs. Every construction project will normally create a safety department, but the rate of accidents is still increasing from year to year. Therefore, the factors to this problem should be examined so that the rate does not increase. The purpose of this study is to find out about the factors of the accidents in construction projects and to look for effective factors in reducing the risks and accidents. The author has used quantitative methods in this study and he has distributed questionnaires to those working in the construction sector. From the results obtained, the author identifies the major problems in the occurrence of accidents in the construction project.